EFFECTIVE WAYS OF TEACHING THE WORKS OF KARAKALPAK WRITERS IN ENGLISH CLASSES - Ibraymova, Z.; Kurbaniyazova, S. (SCIENCE and SOCIETY, 2020)
The article deals with structural studying about teaching literary works in language learning classes, its role in developing learner motivation and the methodological points of teaching the works of Karakalpak writers in English classes.
Keywords: literary works; motivation; methodology; effectiveness; nation; value